Horrid Henry - Simon, Francesca; Ross, Tony (London : Orion Children's Books, 1999)
Horrible Henry causes his brother Perfect Peter all sorts of problems when he behaves properly for a change, upstages Peter at a dance recital, plays pirates, and goes on a camping trip.
"A Dolphin paperback.".
Keywords: Behavior -- Fiction; Brothers -- Fiction; Humorous stories